Akten zur Auswärtigen Politik der Bundesrepublik Deutschland 1984 - Taschler, Daniela (De Gruyter, 2015)
1984 marked a low point in East-West relations. NATO`s deployment of medium-range nuclear missiles in Western Europe as well as the announcement of the Strategic Defense Initiative (SDI) led to a ratcheting up of tensions. The CDE, a conference that sought to build confidence and promote disarmament, first convened in Stockholm in 1984, yet it was not possible to break the deadlock in negotiations over nuclear weapons until after the death of Andropov and Reagan`s election victory. West Germany and France expanded their cooperation during this period as they sought greater European integration as well as the strengthening of the Western European Union (WEU). The West German government in Bonn came under pressure following reports that German firms had assisted Iraq with chemical weapons production. It was also criticized for considering the delivery of tanks to Saudi Arabia. Meanwhile, a growing number of East Germans were taking refuge in Western embassies, seeking to escape the Eastern bloc. This fanned tensions between East and West bowing to Soviet pressure, the East German head of state, Erich Honecker, cancelled a trip to West Germany. The difficult historical burden borne by West Germany was evident during the D-Day memorial ceremony in Normandy as well as during the memorial service attended by Helmut Kohl and François Mitterrand in Verdun. West Germany was exhorted by many nations to shun revanchism and Pangermanism. The 357 documents made available for the first time in this collection address a range of other topics, including the assassination of Indira Gandhi, the wars in Lebanon and the Pesian Gulf, the conflicts in Central America, and the Polish Crisis.